Pharmacokinetics, Mass Balance, Excretion, and Tissue Distribution of Plasmalogen Precursor PPI-1011 - Smith, Tara; Knudsen, Kaeli J.; Ritchie, Shawn A. (Frontiers in Cell and Developmental Biology, 2022)
PPI-1011 is a synthetic plasmalogen precursor in development as a treatment for multiple plasmalogen-deficiency disorders. Previous work has demonstrated the ability of PPI-1011 to augment plasmalogens and its effects in vitro and in vivo, however, the precise uptake and distribution across tissues in vivo has not been investigated. The purpose of this study was to evaluate the pharmacokinetics, mass balance, and excretion of [14C]PPI-1011 following a single oral administration at 100 mg/kg in Sprague-Dawley rats. Further tissue distribution was examined using quantitative whole-body autoradiography after both single and repeat daily doses at 100 mg/kg/day. Non-compartmental analysis showed that following a single dose, PPI-1011 exhibited peak levels between 6 and 12 hours but also a long half-life with mean t1/2 of 40 hours. Mass balance showed that over 50% of the compound-associated radioactivity was absorbed by the body, while approximately 40% was excreted in the feces, 2.5% in the urine, and 10% in expired air within the first 24 hours. Quantitative whole-body autoradiography following a single dose showed uptake to nearly all tissues, with the greatest initial uptake in the intestines, liver, and adipose tissue, which decreased time-dependently throughout 168 hours post-dose. Following 15 consecutive daily doses, uptake was significantly higher across the entire body at 24 hours compared to single dose and remained high out to 96 hours where 75% of the initially-absorbed compound-associated radioactivity was still present. The adipose tissue remained particularly high, suggesting a possible reserve of either plasmalogens or alkyl diacylglycerols that the body can pull from for plasmalogen biosynthesis. Uptake to the brain was also definitively confirmed, proving PPI-1011’s ability to cross the blood-brain barrier. In conclusion, our results suggest that oral administration of PPI-1011 results in high uptake across the body, and that repeated dosing over time represents a viable therapeutic strategy for treating plasmalogen deficiencies.